If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2.3x + 5.4 Reorder the terms: y = 5.4 + 2.3x Solving y = 5.4 + 2.3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 5.4 + 2.3x
| -6(v+3)+3v+7=6v+7 | | 2a-(a+3)+3= | | 2(v+8)+5v=37 | | 9=5(u-3)+3u | | 28=4(w+6)-6w | | 1/9a=6 | | 6(-2-x)=-5(x+3) | | 5x-4-3x=14 | | -4=n | | 4e^3x+2=110 | | 10(s-4)=-132 | | 4e^3x+2=20 | | 10(s-4)=3 | | 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 | | 82=14+2x | | -5(7x+10)=-295 | | 3/4p=114 | | 26/x=13/8 | | y=x^2-17/2 | | 2c+5=3c | | 17x-4=4(4x+5)-16 | | 2c+5=8c | | 4c+6=6c | | 4c+6=6 | | 10x(8x^3+1)=0 | | log(x/5)=3 |